Recombinant CD300c-Ig fusion protein attenuates collagen-induced arthritis in mice. (21st May 2021) - Liu, Haiyan; Zhao, Jin; Su, Min; Tian, Xiaohong; Lai, Laijun
Abstract: Objectives: RA is a chronic autoimmune disease characterized by joint inflammation and tissue destruction. Immune responses mediated by T cells and autoantibodies are known to play critical roles in RA. Collagen type II (CII)-induced arthritis (CIA) is a commonly used animal model of human RA. We have previously reported the identification of a new T cell inhibitory molecule CD300c. Here we investigate the ability of recombinant CD300c-IgG2a Fc (CD300c-Ig) fusion protein to prevent and treat CIA. Methods: Mice were induced to develop CIA by CII and injected with CD300c-Ig or control Ig protein before or after CIA symptoms occur. The mice were examined for CIA clinical and pathological scores, and analysed for the expression of proinﬂammatory cytokines, the percentage and activation of CD4 T cells and regulatory T cells, CII-speciﬁc T cell proliferation and cytokine production, and CII-specific autoantibody production. Results: In a prevention model, CD300c-Ig signiﬁcantly decreases CIA incidence, and reduces clinical and pathological arthritis scores. In the treatment model, CD300c-Ig ameliorates established CIA. The beneficial effects of CD300c-Ig are related to decreased expansion and activation of T cells in the spleen and reduced expression of proinﬂammatory cytokines in the joints. CD300c-Ig also inhibits CII-specific T cell proliferation and Th1 and Th17 cytokine production. In addition, CD300c-Ig treatment reduced the production of CII autoantibodies in the serum. Furthermore, CD300c-Ig inhibits the proliferation and activation of T cells from RA patients in vitro . Conclusion: CD300c-Ig protein has the potential to be used in the treatment of patients with RA.